2014
DOI: 10.4018/ijsda.2014100101
|View full text |Cite
|
Sign up to set email alerts
|

Analysis & Minimization of the Effect of Delay on Load Balancing for Efficient Web Server Queueing Model

Abstract: Load balancing applications introduce delays due to load relocation among various web servers and depend upon the design of balancing algorithms and resources required to share in the large and wide applications. The performance of web servers depends upon the efficient sharing of the resources and it can be evaluated by the overall task completion time of the tasks based on the load balancing algorithm. Each load balancing algorithm introduces delay in the task allocation among the web servers, but still impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…The collected information is used in traffic distribution for improving the performance of web servers. Singh and Kumar [7] suggested that task completion time directly affects the queue length of the web server. They presented a model based on the ratio factor of the task's average completion time.…”
Section: Distributed Queueing Model For Load Balancingmentioning
confidence: 99%
“…The collected information is used in traffic distribution for improving the performance of web servers. Singh and Kumar [7] suggested that task completion time directly affects the queue length of the web server. They presented a model based on the ratio factor of the task's average completion time.…”
Section: Distributed Queueing Model For Load Balancingmentioning
confidence: 99%
“…A polling-based approach is analyzed in reference [31] among the methods applicable to fetching feeds, which is based on a specific schedule for visiting feeds. While the existing polling-based approaches have focused on the allocation of fetching resources to feed in order to either reduce the fetching delay or increase the number of fetched entries, for optimizing both objectives a proposal is present by Singh and Kumar [32].…”
Section: Dynamic Load Balancing Delay Modelsmentioning
confidence: 99%
“…Delay due to load balancing is analyzed in reference [32] based on factors such as average queue length and average waiting time of tasks. Ratio Factor Based Delay Model (RFBDM) is presented, which is an improvement of delay model presented in reference [33].…”
Section: Dynamic Load Balancing Delay Modelsmentioning
confidence: 99%